A Bibliometric Analysis of the International Journal of Energy Economics and Policy: 2013-2022 - Solanki, Sandip; Singh, Seema; Joshi, Meeta (International Journal of Energy Economics and Policy, 2023)
This paper performs a bibliometric analysis of the International Journal of Energy Economics and Policy (IJEEP) for 2013-2022. Bibliometrix R package (R studio) and Scopus database were used for the study and examined 2194 documents published in the journal between 2013-2022. The results showed an upward trend in publications with a yearly growth rate of 21.92%. H. Mahmood is the most relevant author by the number of papers published with the highest h-index, while the most-cited author is A. Mikhaylov. This research revealed that Indonesia is the most productive country in terms of publications, while Malaysia is the most-cited nation. Covenant University is the most productive university in terms of overall publications. The results show that there are 4782 authors’ keywords in total. Of these keywords, “economic growth” is the top keyword, with more than 293 occurrences. Intellectual and social structures highlighted collaborations amongst authors, institutes and countries.